IMPLEMENTASI KEPUTUSAN GUBERNUR KEPALA DAERAH TINGKAT I BALI NOMOR 394 TAHUN 1997 DALAM MEMBERIKAN PERLINDUNGAN HUKUM BAGI SEKAA/ ORGANISASI KESENIAN - I MADE BADRA (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2012)
In order to create order and legal certainty to the type and quality of local artsto tourism, the Government of Bali Province issued the Regional Decision of TheGovernor of The Head of Bali Number 394 of 1997 on Regulating Regional Arts onThe Province of Bali. Implementation of the Regional Decision of The Governor ofThe Head of Bali Number 394 of 1997 on Regulating Regional Arts on The Provinceof Bali of the terms, procedures and sanctions do not work effectively. These arecaused because of legal substance, legal structure, legal culture and the means andfacilities. To optimize the decision made by the Governor of the preventive andrepressive efforts. To streamline the implementation of the Regional Decision of TheGovernor of The Head of Bali Number 394 of 1997 will require a synergy betweenthe Department of Culture, sekaa / arts organizations and the service users. RegionalDecision of The Governor of The Head of Bali Number 394 of 1997 should have tobe amended because it does not fit with the times. Bali Provincial Cultural Officeshould be more proactive in doing preventive and repressive efforts in upholding theRegional Decision of The Governor of The Head of Bali Number 394 of 1997.